Evaluación de una dieta a base de harina de lombriz en la alimentación del hámster ruso, en la ciudad de Latacunga, año 2015 - Cajas Rodríguez, Edison Andrés (2015)
The objective of this research was to evaluate two levels of protein in the diet of Russian hamster, individuals 21 days old. 30 specimens were acquired and trained, completely random, two groups of 15 animals. The initial weight was recorded and then weekly for each of the individuals. With the results, we conclude that treatment 1 with a gain of average final weight of 19.13 g was reached, while Treatment 2 (control) average gain of 17.73 g final weight was reached. Greater weight gain in the treatment 1 is determined. The difference revolves it had as main meal worm obtained by dehydration of the same component. Treatment 2 contains soya. In addition, the economic analysis of production costs, determines the treatment 1 is cheaper. He had a final cost of $ 83, while treatment 2 was $ 89. With a difference of $ 6 between the two treatments....